Rape and the legal process - "Temkin, Jennifer" (London, 1987)
Public disquiet has been intermittently but vehemently expressed about the crime of rape and the way it is handled by the criminal justice system. But in the 21st century the legal process still fails to provide an adequate response to sexual violation and abuse. This text examines some of the difficulties which this crime presents and analyses in detail how the legal system could and should be addressing them. Central issues considered include the experience of rape victims, their treatment by the police and the courts and the inadequacies of the present law and the rules of evidence surrounding it. Changes enacted in many different jurisdictions, such as schemes for legal representation for victims of sexual violence are evaluated.
Keywords: Rape-Law and legislation-England